Culture of Banjarese Represented in Their Language - Yusuf Al Arief (International Journal of Southeast Asian Studies (IJSAS), 2022)
Culture and language are like two sides of a coin. Both represent each other in unique ways. Therefore, understanding a certain culture can be achieved by understanding people's language. This research objective was to describe the representation of Banjarese culture in their daily language use. This paper was written as descriptive qualitative research, and the observation method and interview were used to collect the data, and it was analyzed based on an Anthropolinguistics point of view. The author found that the Banjarese language portrayed the culture of the Banjarese people. It was represented in the phonological form, the concept of respect, faith, and literary works.